TikTok-Based Multimodal Input for Vocabulary Development in Writing - Nur Habibah Sueb; Sumarta; Kamalia hakim, Putri (Universitas Islam Negeri Raden Intan Lampung, 2026)
Vocabulary plays a fundamental role in developing students’ writing skills, yet many English as a Foreign Language (EFL) learners struggle to express ideas due to limited vocabulary knowledge. Although TikTok has increasingly been used as a language learning platform, limited research has explored how its multimodal features support vocabulary development in writing. Therefore, this study aimed to investigate how TikTok-based multimodal input supports students’ vocabulary development in writing at SMK Budi Mulia Karawang. This study employed a qualitative case study involving 24 tenth-grade students. Data were collected through classroom observations, vocabulary worksheets, semi-structured interviews with four students, and analysis of six students’ writing samples. The learning activities involved watching a Rapunzel video from the TikTok account @storytimeon321, identifying and recording unfamiliar vocabulary, and constructing sentences using the newly learned words. Data were analyzed using Braun and Clarke’s (2006) thematic analysis The findings revealed that TikTok-based multimodal input facilitated vocabulary acquisition, recognition, retention, and productive vocabulary use in writing. Visual elements, audio, and captions helped students understand word meanings, improve pronunciation, recognize vocabulary, and retain newly learned words. Furthermore, students demonstrated increased motivation and successfully transferred newly acquired vocabulary into meaningful written sentences. Overall, TikTok-based multimodal learning provides contextualized learning experiences that effectively support vocabulary development and enhance EFL students’ writing skills.